The Impact of Contextual Learning and Learning Interest in Prayer Material on Islamic Education Subjects - Achadah, Alif; Laksana, Sigit Dwi; Triyuliasari, Anisah; Chandra, Agni Tyas Nursata; Zukhrufin, Fina Kholij (Al-Hayat: Journal of Islamic Education, 2025)
This research aims to explain and analyze the influence of Contextual Teaching Learning (CTL) on student learning outcomes in Islamic Education subjects by selecting the research locus at State Junior High School 1 Sambit, Ponorogo. This research is quantitative research with a descriptive approach. The population in this study was 102 students in seventh grade. A simple random sampling technique was used to obtain a sample of 52 students. Data collection techniques used were questionnaires, interviews, and documentation. To determine the data collection instrument, use a Likert scale. Data analysis techniques used regression equations, regression significance tests, and regression linearity tests. The findings of this research are that CTL learning has a significant effect on the learning outcomes of seventh-grade students in Islamic Education, and interest in learning has a significant effect on the learning outcomes of Class VII students in Islamic Education. There is an influence by the learning variables Contextual Teaching Learning and interest in learning of 71.7% on the student learning outcomes variable, while the other 28.3% can be explained by other variables outside the model. This study shows that Contextual Teaching and Learning and students' learning interests have a positive and significant effect on the learning outcomes of Islamic Education of seventh-grade students at State Junior High School 1 Sambit, with CTL as the most dominant factor. The originality of this finding lies in the application of CTL in the local context and religious subjects, which are rarely studied, as well as the integration of students' cognitive and affective aspects through a contextual learning approach that involves spiritual reflection and worship practices. This approach strengthens the relevance of CTL not only in academic learning but also in the formation of students' values and characters.